KEPEMIMPINAN AFILIATIF KEPALA SEKOLAH PADA PENGELOLAAN PENDIDIK DI SMA NEGERI 1 SANDAI - Wati, Erna; Asrori, M; Radiana, Usman (Jurnal Visi Ilmu Pendidikan, 2025)
AbstractThis research aims to describe the affiliative leadership of the principal in the management of teaching staff at SMA Negeri 1 Sandai. The form of research used is qualitative research with a case study approach. The participants in this study consist of 7 individuals: 4 males aged between 38 - 49 years, and 3 females aged between 47 - 58 years. All subjects are principals, vice principals in charge of curriculum, and educators. Data collection methods use observation, interviews and documentation The data validity checking technique uses triangulation.The main findings in this research indicate that: (1) the school principal's affiliative leadership builds strong interpersonal relationships among the teaching staff. 2) the school principal's affiliative leadership empathizes with the teaching staff. (3) the school principal's affiliative leadership communicates effectively with the teaching staff.. The conclusions in this research are: (1) in improving affiliative leadership, a leadership approach that emphasizes building strong interpersonal relationships between leaders and team member. (2) the first implementation is to show empathy, understanding and sincere concern for the welfare of team members, who are part of the team making contributions from teaching staff, which is an advantage in carrying out affiliative leadership activities (3) interpersonal communication in affiliative leadership. The implication is that by applying affiliative leadership, the principal of SMA Negeri 1 Sandai can enhance teachers' motivation and performance, create a harmonious work culture, encourage innovation in teaching, strengthen collaboration among educators, and increase teachers' loyalty to the school. This will foster a conducive work environment and positively impact the quality of education at the school.Key Word: Leadership, Affiliate, Educator